2015
DOI: 10.1177/2325967115584883
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Health Insurance Status on the Timing of Surgery and Treatment of Bucket-Handle Meniscus Tears

Abstract: BackgroundLack of insurance has been shown to lead to delays in seeking care as well as fewer preventive medicine visits and poorer overall health status.PurposeTo investigate the effects of insurance status on the timing and treatment of patients with bucket-handle meniscus tears.Study DesignCohort study; Level of evidence, 3.MethodsCharts from 2004 to 2013 were retrospectively reviewed for patients diagnosed with bucket-handle meniscus tears. Patients were divided into 2 groups: insured or underinsured. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Patients with Medicaid insurance were found to have significantly increased lag times from initial dislocation to initial office consultation and surgery. These findings are similar to those previously reported for patients with anterior cruciate ligament and meniscal injuries, where Baraga et al 2 and other studies 8,21,23,30 have described delays in both diagnosis and surgical treatment of patients without private insurance. It is not known whether the patients in this study who experienced significant delays between their first instability event and evaluation at our institution attempted to obtain care elsewhere during this interval and, if so, whether they were successful in doing so.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Patients with Medicaid insurance were found to have significantly increased lag times from initial dislocation to initial office consultation and surgery. These findings are similar to those previously reported for patients with anterior cruciate ligament and meniscal injuries, where Baraga et al 2 and other studies 8,21,23,30 have described delays in both diagnosis and surgical treatment of patients without private insurance. It is not known whether the patients in this study who experienced significant delays between their first instability event and evaluation at our institution attempted to obtain care elsewhere during this interval and, if so, whether they were successful in doing so.…”
Section: Discussionsupporting
confidence: 91%
“…Previous authors have found that insurance coverage affects timeliness of care for patients with anterior cruciate ligament injuries and meniscal tears, noting that patients with private insurance undergo surgery more expeditiously than those without. 2,21,30 In 2015, 9.1% of all Americans were uninsured and 19.6% had Medicaid. 3 With a limited number of providers accepting Medicaid, patients enrolled in Medicaid as well as those without insurance may have difficulty obtaining office visits and scheduling elective surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Few case reports or clinical studies with limited cohort sizes of repair of bucket-handle meniscus tears exist in the literature, and limited studies clearly define the patient demographics and compare preoperative or intraoperative surgical variables in those with successful repair or failed repair. 4,[9][10][11][12][13][14] The purpose of this study was to evaluate a single academic institution's cohort of patients with buckethandle meniscus tears who underwent arthroscopic repair. Specifically, we sought to (1) report patient demographic information for those who sustained bucket-handle meniscus tears; (2) evaluate patient clinical outcomes, return to sport, complications, and reoperation/revision rates after arthroscopic repair of bucket-handle meniscus tears; and (3) to compare the subgroups of patients with successful outcomes to those with failure after repair in order to identify any correlative patient-related, surgical techniquerelated, or pathology-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…23,25 Surgical treatment before the onset of progressive disease and meniscal degeneration decreases the likelihood of unfavorable subjective outcomes and radiographically detectable osteoarthritis. 1,12,13,22 Although a specific timeline of repair has not been established, Sood et al 21 demonstrated that patients with traumatic bucket-handle meniscal tears had a greater rate of successful repair when surgery was performed within 6 weeks of the injury.…”
mentioning
confidence: 99%